Distribution of Organic Food in Poland - Joanna Smoluk-Sikorska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Distribution of organic food in Poland has a number of weaknesses resulting from low and irregular supply as well as dispersion of producers and intermediaries. The paper presents the outcomes of research carried out in 2012 in three types of retail outlets offering organic food, i.e. specialist shops, groceries and retail networks. The investigation was conducted in the form of in-depth interviews using a standardised questionnaire. As the research shows, only in specialist stores does the product range satisfy consumer needs, whereas in the other outlets it is limited generally to processed products. Wholesalers, organic farms and brokers are the main providers of the surveyed retail outlets; nevertheless, specialist shops use the services of more providers than the other types of outlets. Low supply of organic food results in high retail prices. Specialist shops and groceries apply margins up to 40% on average, while retail networks have margins up to 20%.